Նորակազմ բառերը արդի հայերենի բառապաշարում - Գալստյան, Ա. Ս.
В статье рассматриваются разные аспекты образования новых слов – неологизмов в современном армянском языке, выделяются основные модели их образования, исходя из материалов книги “Новые слова” (вып. I-V, Ереван, 2015-2020). The article discusses different aspects of the formation of new words - neologisms in the modern Armenian language and highlights the main models of their formation, based on the materials of the book "New Words" (issues I-V, Yerevan, 2015-2020).
Keywords: Լեզվաբանություն